Análise do Conselho de Administração da BRF S.A. como um campo de ação estratégica - Oliveira, Victor Tadeu de (2019)
In the context of Global Financialization, companies are now guiding their actions in order to deliver the largest possible dividends to their shareholders. In this sense, there are problems of agency, which are solved with Corporate Governance. One of its main elements is the Board of Directors, which represents the shareholders in monitoring the actions of management. In this study, we analyzed the Board of Directors of BRF S.A. as a Strategic Action Field during the rise until the fall of the businessman Abílio Diniz in his command, and the changes occurred from external shocks, besides the behavior of the incumbent and challenging groups, and using concepts of shareholder activism.